Islamic notion of happiness (Al-Sa‘ada): an analysis of Miskawayh’s thought - Mohd. Nasir Omar; Ahmad Sunawari Long; Abdull Rahman Mahmood; Zaizul Ab Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Miskawayh (d.1030), through his famous book on ethics, Tahdhib al-Akhlaq (The Refinement of Character), has separated ethics from other disciplines, offering a very thorough analytical system of Islamic ethics. His Tahdhib al-Akhlaq was thus occupying a prominent place in this particular branch of Islamic ethical literature. It is scarcely an exaggeration to say that most of the later works that deal with this subject such as those by al-Ghazali, al-Tusi and al-Dawwani, use it as their main authority and some of them are even based on it. Thus, the objective of this qualitative study, which applies conceptual content analysis method, is to make a critical analysis of such an influential works on ethics in Islam with the purpose of elucidating its views concerning happiness, as well as the ways by which man may achieve a noble state of character, so as to attain such a great goal. To this end, the present study confines itself to discussing the concept of happiness and to finding out the answer to those particular questions regarding its nature such are, what is meant by happiness, or what does happiness consist of? Why is happiness the end to be achieved by man and for which sake he was created? Is happiness attainable in this life or the next? Who is the happy man? and so forth. The result of this study shows that the thought of Aristotle and other philosophers enable Miskawayh to philosophise about moral happiness and how Islamic faiths brings about the development of that legacy.